The Influence of Leadership on Motivation and Performance of Employees in Kunto Darusalam District, Rokan Hulu Regenc - Dedy Saputra; Sopiah Sopiah (Institute of Computer Science (IOCS), 2021)
This research intends to determine the effect of leadership on the motivation and performance of employees in the District of Kunto Darussalam, Rokan Hulu Regency. The research was conducted from September to October 2019. The source of the research data was obtained from respondents who worked in Kunto Darussalam District, Rokan Hulu Regency. With 39 samples as research respondents. Data analysis in the form of validity and reliability tests, hypothesis testing using SEM - PLS and the coefficient of determination. The results: Sub structure 1 shows that leadership (X) has a significant effect on motivation (Y1) and leadership (X) has a positive and significant effect on employee performance (Y2), and motivation (Y1) has a positive and significant influence on performance. employee (Y2) Kunto Darussalam District, Rokan Hulu Regency. Furthermore, sub-structure 2, namely leadership (X) has an indirect effect on employee performance (Y2) Kunto Darussalam District, Rokan Hulu Regency through motivation (Y1) produces a significant positive effect.